Digital Literacy in Islamic Higher Education Instruction: Exploring Innovative Approaches to Curriculum Integration - Al Musanna; Herwanis, Delfia; Zakaria, Rahmanita; Wahyuni, Septia (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study examines the integration of digital literacy into Islamic higher education instruction through the implementation of blended learning at the State Islamic Institute of Takengon. Using a mixed-methods design, the research involved 30 participants (10 students, 10 lecturers, and 10 administrators) selected through stratified random sampling. Quantitative data were collected through structured questionnaires, while qualitative data were obtained from semi-structured interviews and focus group discussions. The findings reveal that participants demonstrate strong proficiency in basic digital skills such as word processing and internet navigation, yet show limited competence in advanced skills, including digital content creation and critical evaluation of digital sources. Blended learning emerged as an effective pedagogical strategy for embedding digital literacy into Islamic studies courses, particularly in Ulumul Qur’an and Ulumul Hadits. However, infrastructural limitations, insufficient professional development, and institutional resistance remain significant challenges. The study offers a contextual model of digital literacy integration grounded in Islamic educational values and highlights the importance of structured digital pedagogy training and improved technological infrastructure. These findings provide practical and policy-oriented recommendations for strengthening curriculum innovation in Islamic higher education.